Tourism, water resources and urban sustainability A case study of the impact of tourism on development Agchay dam, sustainability and income in Chayparhcity - Rostami, Ghahraman (Pure and Applied Science Advances, 2014)
Thehigh number of towns and settlements has a very top of their undeniable role inthe lives of the vast expanse of land, which is so important in the study andplanning of sustainable development and more measured information should be decided.However, the use of past experiences and proper planning for the futurerequires a correct summation of past experiences and needs logical assessmentof the situation in the future. Therefore, Recognition of villages and citiescan be considered as one of the most important parts of sustainable development.Nowadays The researches ofrural and urban community are important in knowing the advancing the country’s development goals So, to reviewthe (Qarezyaaddin)City has been studiedfrom the viewpoint of economy and living conditions. (Qarezyaaddin) center ofChayparh city has been chosen as one of the target cities due to Bastam historic castles and Agh Chai dam,which is the first aristocraticarch dam disclosed tofertile lands.to do this study, library and field methods through interviewswith target groups has been used.These results indicate that Qarezyaaddin has arich economic potential of the city native livestock and agricultural fields.This result indicates that theincreased revenue from tourism, livestock and agriculture sectors stronglyinfluenced the city.And it has become a dynamic city So that rapid changes inurban development in recent years isvery impressive compared to surrounding towns.satellite maps shows this fact.